Novel cardiovascular magnetic resonance oxygenation approaches in understanding pathophysiology of cardiac diseases. (19th February 2018) - Sree Raman, Karthigesh; Nucifora, Gaetano; Selvanayagam, Joseph B
Summary: Cardiovascular magnetic resonance imaging (CMR) permits accurate phenotyping of many cardiac diseases. CMR's inherent advantages are its non‐invasive nature, lack of ionizing radiation and high accuracy and reproducibility. Furthermore, it is able to assess many aspects of cardiac anatomy, structure and function. Specifically, it can characterize myocardial tissue, myocardial function, myocardial mass, myocardial blood flow/perfusion, irreversible and reversible injury, all with a high degree of accuracy and reproducibility. Hence, CMR is a powerful tool in clinical and pre‐clinical research. In recent years there have been novel advances in CMR myocardial tissue characterization. Oxygenation‐sensitive CMR (OS‐CMR) is a novel non‐invasive, contrast independent technique that permits direct quantification of myocardial tissue oxygenation, both at rest and during stress. In this review, we will address the principles of the OS‐CMR technique, its recent advances and summarize the studies in the effects of oxygenation on cardiac diseases.